Baruch Spinoza and the Ethics of Care: Towards A Monistic Understanding of Spiritual Care at the End of Life - Giménez Lorente, Daniel (Nursing philosophy, 2026)
Dualism has shaped current healthcare based on the dichotomies of body-mind, science-spirituality and life-death, consolidating a biomedical paradigm that treats the patient as an object, marginalising the spiritual dimension. This article explores Baruch Spinoza's philosophy as an alternative to the ethics of nursing care, integrating the physical, emotional, and spiritual dimensions within the same ontological continuum. Through a philosophical-conceptual approach inspired by hermeneutic interpretation, key concepts from the work Ethics are presented, inviting the reader to reflect on them in the nursing context of spiritual care at the end of life. In Spinoza, life and death are expressions of the same necessary order of Nature, and freedom arises from understanding that necessity. From this perspective, caring for the dying becomes an affective, collective and rational act, based on knowledge of the natural order. Spinozian philosophy allows us to conceive of care as an ontological-existential mode that is relational, structural, and immanent. Nurses participate in the process of human interdependence and expand the power to act. Understanding the rational transformation of emotions provides tools for accompanying suffering. A Spinozian ethic of care restores a holistic and affirmative view of life to nursing, unifying spirituality and reason.